Random lasing action generation in polymer nanofiber with small diameters. (25th May 2018) - Lv, Gang; Huang, Dengfeng; Wu, Shibin; Ren, Ge; Yang, Wei; Li, Tingshuai
Abstract: The light-propagation ability of fiber depends mostly on fiber diameter. Fibers with a diameter below 200 nm have poor capability of exhibiting light coupling and laser radiation. Therefore, we modified nanofibers with a diameter of 150 nm by nanoparticle doping and morphological modification to enhance scattering. A finite-difference time-domain method was used to analyze the coupling of light into fibers and its possible distribution. The simulations demonstrated that single and multiple modes were highly influenced by the diameter values. The results of the study contribute to the realization of random lasers in nanofibers with extremely small diameters.